Sphagnum cuspidatulum extract prevents acute kidney injury induced by high-fat diet and streptozotocin via alleviation of oxidative stress and apoptosis in pre-diabetic rats - Pongrapee Laorodphun; Sutheera Chaisen; Sarocha Amattat; Pornchita Maphet; Narin Printrakul; Hataichanok Pandith; Aussara Panya; Burit Kongmali; Myat Theingi Swe; Phatchawan Arjinajarn (Frontiers Media S.A., 2024)
ContextObesity and pre-diabetes are associated with renal dysfunction via elevated oxidative stress. Peat moss, or Sphagnum cuspidatulum Müll. Hal., Sphagnaceae (SC), are rich in phenolic compounds that enhance antioxidant activity.ObjectiveSC might show beneficial effects in pre-diabetes-associated renal dysfunction.Materials and methodsMale Wistar rats, after 4 weeks on a high-fat diet, received low-dose streptozotocin to induce pre-diabetes. Then, the pre-diabetic rats were randomly divided into 4 groups: untreated pre-diabetic rats (P-DM), pre-diabetic rats treated with SC 50 or 100 mg/kg/day (P-DM50 or P-DM100), and pre-diabetic rats treated with metformin 100 mg/kg/day (MET). The drugs were fed by gavage for 4 weeks.ResultsTreatment with SC100 dramatically lowered serum creatinine (S.Cr.), blood urea nitrogen (BUN), and augmented creatinine clearance in pre-diabetic rats. Additionally, SC100 significantly decreased the malondialdehyde level. Furthermore, pre-diabetic rats treated with SC100 significantly upregulated the expression of nuclear factor erythroid 2-related factor 2 (Nrf2) and its downstream mediators, with downregulated apoptotic markers.Discussion and conclusionOur findings provide a scientific basis for the clinical application of SC and a new strategy for the prevention of nephrotoxicity and other kidney disease in the future.